Teacher Readiness for Digital Competence in TVET Education at Vocational Colleges - Latepi, Nik Nur Hafizah; Madar, Ahmad Rizal (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study aims to identify the level of skills, knowledge and attitudes of technical instructors towards their readiness in mastering the competencies of the digitization system in TVET education with a focus on four Vocational Colleges namely Muar Vocational College, Kluang Vocational College, Batu Pahat Vocational College and Segamat Vocational College. The study uses a quantitative approach through data collection using a questionnaire involving 145 respondents from among technical instructors at the Vocational College involved. The results of the study found that the knowledge of technical instructors is at a moderate to high level, where they understand the basic concepts of digitization systems but lack exposure to advanced technology and more complex digital applications. The skill level was found to be at a moderate level with most teaching staff showing basic ability in using digital technology such as online learning software, but facing difficulties in handling more technical and specific software. In terms of attitude, the majority of teaching staff showed openness and a positive attitude towards the use of technology with a willingness to learn and integrate digitization systems in their teaching. However, this study also identified some challenges faced by teaching staff including time constraints to learn new technology, lack of ongoing technology training as well as limited access to facilities and digital equipment in the Vocational Colleges involved. This study also confirmed that there is a significant relationship between knowledge, skills and attitudes where an increase in one of these elements can strengthen the other elements. Therefore, this study emphasizes the need to comprehensively improve technology training, increase access to digital infrastructure, and provide continuous support to strengthen the readiness of technical teaching staff to face the challenges of digitization in TVET education. The results of this study provide important guidance to the management of Vocational Colleges to formulate a more comprehensive and effective strategy in improving the digital competence of teaching staff in line with the increasingly digital and high-tech TVET education needs. The readiness of teaching staff towards digitization in TVET education in Vocational Colleges is positive, but still needs to be strengthened with continuous training and adequate infrastructure. Support from institutions, industry and government is very important to ensure this transformation is successful. With a holistic approach, digitization can improve the quality of teaching and prepare teachers and students to face the technological challenges of the future.